DETERMINATION OF TRACE METALS INMAHAWEEL RIVERSEDIMENTS BY ACID EXTRACTION - Al-Zahawie, Suha K (Al-Nahrain Journal of Science, 2018)
In this study, a boiling mixture of acids (20% HCl + 80% HNO3) was used to extract trace metals from sediments for Mahaweel River (branch of Euphrates). The elements of interest included Na, Mg, Ca, Cr, Cu, Pb, Hg and Ni, all of which can be determined by electro thermal atomic absorption spectrometry (ETAAS). High recoveries percentage 96, 97, 99, 99, 97.5 and 95 for Na, Mg, Ca, Cr, Cu, and Pb, respectively. The relative standard deviation of the method is less than 3%. Calibration graphs for Pb, Ni and Cr were found to be linear between 100-250, 80-180, 180-250 ng/mL, respectively However, when the acid extraction method was applied to some selected sediments, the resulting trace metal concentrations, although reproducible. Apparently SRM-1645 provided too favorable an assessment of the true accuracy of the method with ordinary sediments.